Artificial Intelligence and Digital Sovereignty: The European Model (BioLaw Journal - Rivista di BioDiritto, 2026)
This document aims to analyse the relationship between European legislation and artificial intelligence, its distinctive features and the paradigms on which it is based. Specifically, this contribution intends to examine the philosophical-legal model of regulatory sovereignty that emerges in the light of European legislation on artificial intelligence. The European model of technological humanism shows an innovative approach that concerns, on the one hand, the relationship between law and technology and, on the other, the relationship between human beings and artificial intelligence. This model, based on legal protection by design, a risk-based approach, human oversight and explainability, marks an evolution in legal solutions and tools capable of innovating traditional paradigms.
Keywords: artificial intelligence; digital sovereignty; European regulation; national regulation; technological humanism